2021
DOI: 10.1080/14756366.2021.1879803
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of novel heterofused 1,2,4-triazine derivative in colorectal cancer

Abstract: Colorectal cancer (CRC) is the third leading cause of cancer-related deaths in men and in women. The impact of the new pyrazolo [4,3-e]tetrazolo [1,5-b][1,2,4]triazine sulphonamide (MM-129) was evaluated against human colon cancer in vitro and in zebrafish xenografts. Our results show that this new synthesised compound effectively inhibits cell survival in BTK-dependent mechanism. Its effectiveness is much higher at a relatively low concentration as compared with the standard chemotherapy used for CRC, i.e. 5f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…Genetic similarities with humans lead to zebrafish often being used as a strong and cost-effective animal model for cancer research and the discovery of cancer drugs. The small size, transparency of zebrafish embryos, easy manipulation, short testing period, and small amount of tested drugs are undoubtedly important aspects giving zebrafish an advantage over the mouse/rat model of cancer [ 36 ]. An antiproliferative test showed that PtMet2–PAMAM possessed the most biological activity, which was much higher than that of PtMet2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic similarities with humans lead to zebrafish often being used as a strong and cost-effective animal model for cancer research and the discovery of cancer drugs. The small size, transparency of zebrafish embryos, easy manipulation, short testing period, and small amount of tested drugs are undoubtedly important aspects giving zebrafish an advantage over the mouse/rat model of cancer [ 36 ]. An antiproliferative test showed that PtMet2–PAMAM possessed the most biological activity, which was much higher than that of PtMet2.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryos were obtained from mating adults, maintained, and raised as described previously [ 36 ]. Zygote period cleaving eggs were transferred to six-well plastic cell culture plates filled with embryo medium E3.…”
Section: Methodsmentioning
confidence: 99%
“…The starting material for the preparation of the new tricyclic sulfonamide MM131 was the corresponding chlorosulfone derivative 1 (Scheme 1) which was obtained by multistage synthesis according to the procedures described in the literature [25][26][27][28][29][30][31]. Thus, obtained compound 1 was mixed with the (R)-enantiomer of 2-amino-propan-1-ol in anhydrous acetonitrile at room temperature.…”
Section: Chemistrymentioning
confidence: 99%
“…When the tumors reached a diameter of about 5 mm, that is, according to the literature the size suitable to conduct further phases of research, the intraperitoneal administration of MM-129 (2.5 mg/kg), 5-FU (50 mg/kg), or their combination was started [28]. The dose was chosen based on our preliminary study, in which we assessed the anticancer activity of MM-129 [9,29]. The control group was administered with MM-129 solvent (10% DMSO/PBS).…”
Section: Establishment Of Xenograftmentioning
confidence: 99%
“…Our previous in vitro observations have clearly shown that MM-129 is more effective than the hitherto used preparations, including the reference drug 5-fluorouracil. It statistically significantly reduces cell viability and inhibits DNA biosynthesis of DLD-1 and HT-29 colorectal cancer cell [9]. The phosphoinositide-3-kinase (PI3K)/AKT/mTOR pathway plays a key role in the regulation of processes related to cell growth, metabolism, survival, and proliferation.…”
Section: Introductionmentioning
confidence: 99%